2018
DOI: 10.1016/j.midw.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

What is next? Midwifery education building partnerships for tomorrow's maternal and neonatal health care

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(29 reference statements)
0
2
0
1
Order By: Relevance
“…The current study indicated insufficient transfer of research findings into midwifery practice, although this varied regionally within countries. Two important influencing factors were highlighted: Firstly, the lack of clinical academic midwives, their recognition and influence, in maternity care practice in many countries 34 . This might be linked to the chosen model of academisation, which differs from the medical model.…”
Section: Discussionmentioning
confidence: 99%
“…The current study indicated insufficient transfer of research findings into midwifery practice, although this varied regionally within countries. Two important influencing factors were highlighted: Firstly, the lack of clinical academic midwives, their recognition and influence, in maternity care practice in many countries 34 . This might be linked to the chosen model of academisation, which differs from the medical model.…”
Section: Discussionmentioning
confidence: 99%
“…Hal tersebut, bertujuan untuk mendukung kebutuhan kesehatan ibu dan bayi di masa yang akan datang. (Luyben, Barger, Avery, & Bick, 2018) Kegiatan pendidikan kebidanan diimplementasikan sesuai dengan kurikulum yang mencakup proses belajar mengajar mulai dari perencanaan pembelajaran oleh dosen, administrasi hingga persiapan sarana dan prasarana yang baik untuk bahan materi teori maupun praktik. Namun, pengembangan kurikulum kebidanan perlu untuk diperhatikan dengan baik karena jika implementasi pengembangan kurikulum ini tidak berkualitas maka akan menghasilkan lulusan yang tidak sesuai dengan kompetensi dan kebutuhan pengguna hingga dapat meningkatkan pengangguran (Elmeida, Dkk., 2013).…”
Section: Pendahuluanunclassified
“…This care has been Adopted by England, Belgium (7) and Australia (19). This implementation approach proved beneficial where women have choices and positive care experience (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%